Fire design methodologies for cold-formed steel beams made with open and closed cross-sections - Laím, Luís; Rodrigues, João Paulo C. (Engineering structures, 2018)
•New fire design methodology for cold-formed steel flexural members is presented.•New formulae for lateral–torsional buckling of unrestrained members is proposed.•Moment capacity results were compared with available fire design predictions.•European fire design rules were found to be unsafe or over-conservative. This paper focuses on developing a simplified fire design methodology for single and built-up cold-formed steel beams based on the European guidelines. Open and closed cross-sections made with (lipped and unlipped) channel sections were selected for this research work. Existing experimental tests and shell finite element analysis using an advanced commercial program were used as the basis for the novel study conducted herein. Numerical results were then compared with predictions from available European fire design rules and appropriate recommendations are made. Such design rules were found to be unsafe or over-conservative depending on the relative slenderness and serviceability load of the beams. Comparisons with numerical moment capacities also demonstrated good precision of the new fire design methodology. The results obtained by this methodology may have an average error of half of those obtained by using the available European design curves.